2014
DOI: 10.1088/0029-5515/54/2/023004
|View full text |Cite
|
Sign up to set email alerts
|

Scaling mechanisms of vapour/plasma shielding from laser-produced plasmas to magnetic fusion regimes

Abstract: The plasma shielding effect is a well-known mechanism in laser-produced plasmas (LPPs) reducing laser photon transmission to the target and, as a result, significantly reducing target heating and erosion. The shielding effect is less pronounced at low laser intensities, when low evaporation rate together with vapour/plasma expansion processes prevent establishment of a dense plasma layer above the surface. Plasma shielding also loses its effectiveness at high laser intensities when the formed hot dense plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…However, we used 1064 nm laser excitation for this study and hence the majority of the laser energy will be coupled to the plasma rather than the target material after the plasma generation. Previous laser breakdown studies showed that nearly 90% of the energy will be absorbed by the plasma after its generation [15], which is consistent with the recent modelling results of plasma shielding during laser exposure [16]. Hence the energy density coupled to the target will considerably be less than the given value.…”
Section: Resultssupporting
confidence: 86%
“…However, we used 1064 nm laser excitation for this study and hence the majority of the laser energy will be coupled to the plasma rather than the target material after the plasma generation. Previous laser breakdown studies showed that nearly 90% of the energy will be absorbed by the plasma after its generation [15], which is consistent with the recent modelling results of plasma shielding during laser exposure [16]. Hence the energy density coupled to the target will considerably be less than the given value.…”
Section: Resultssupporting
confidence: 86%
“…Additional power handling capabilities such as evaporative cooling [6,7] and the vapor shielding effect [8,9] are inherently available for a liquid surface. The concept of vapor shielding encompasses several physical processes.…”
Section: Self-regulated Plasma Heat Flux Mitigation Due To Liquid Sn mentioning
confidence: 99%
“…Additional heat transport by convective movement of the liquid, evaporative cooling 7 and a reduction of neutron issues 8 are other potentially beneficial properties of liquid PFCs. Finally and most importantly, when operating in the vapour shielding regime where a cloud of evaporated neutrals exists in front of the plasma-exposed surface 9 , 10 , any accidental exhaust power excursion leads to increased evaporation, which may mitigate the impact on the divertor armour by self-protection. Despite these advantages, liquid metals are still at a low technology readiness level and require further development.…”
Section: Introductionmentioning
confidence: 99%